2017
DOI: 10.1007/s11270-017-3449-7
|View full text |Cite
|
Sign up to set email alerts
|

Brown Algae and Basalt Meal in Maintaining the Activity of Arylsulfatase of Soil Polluted with Cadmium

Abstract: This study analysed the effectiveness of innovative (basalt meal, brown algae extract) and conventional (barley straw) substances which hypothetically alleviate the inhibiting effect of Cd2+ on biochemical properties of soil, with particular regard to the activity of arylsulfatase. An analysis of their potential was carried out based on the activity of arylsulfatase and the number of Pseudomonas sp. determined on the 25th and 50th days of the study. Cd2+ was applied in the following doses: 0, 4, 40, 80, 120, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…This study demonstrated a negative effect of cadmium on enzymatic activity of soil. Zaborowska et al (2017) also noted an adverse effect of cadmium applied at 40 to 200 mg kg −1 d.m. of soil on the activity of arylsulphatase, which deepened with an increasing level of soil contamination with Cd 2+ .…”
Section: Biochemical Physical and Chemical Properties Of The Soilmentioning
confidence: 95%
“…This study demonstrated a negative effect of cadmium on enzymatic activity of soil. Zaborowska et al (2017) also noted an adverse effect of cadmium applied at 40 to 200 mg kg −1 d.m. of soil on the activity of arylsulphatase, which deepened with an increasing level of soil contamination with Cd 2+ .…”
Section: Biochemical Physical and Chemical Properties Of The Soilmentioning
confidence: 95%
“…Application to the soil of a sequence of experimental variables was preceded with soil fertilisation suitable for the specific crop. The form of fertilisation is described by Zaborowska et al (2017) and the fertilisation rate, expressed as a pure nutrient, was N 250, P 50, K 90, Mg 20, Cu 5, Zn 5, Mo 5, Mn 5 and B 0.33 (mg kg −1 of soil). The potential inhibition was analysed based on four major factors: (1) the degree of soil contamination with BPA: 0, 0.1, 2, 40, 800 mg BPA kg −1 DM of soil;…”
Section: Design Of Pot Experimentsmentioning
confidence: 99%
“…However, research in which the BPA toxicity for plants was determined even at the level of 1000 mg BPA kg −1 DM of soil contamination (Kim et al 2018) was conducted. One of the manifestations of its complex nature is the process of BPA glycosylation induced in plants, which produces secondary metabolites of mono-and di-O-β-dglucopyranosides without the oestrogen activity (Zaborowska et al 2017;Nakajima et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The close relationship between environmental pollution and abiotic stress has been documented in several studies in field (e.g., Alshaal et al 2017;Balakhnina and Nadezhkina 2017;Giron-Calva et al 2017;Hasanuzzaman et al 2017) or in in vitro studies (e.g., Leung 2017). So, several publications have been issued about the pollutants in the environment such as arsenic (Gupta and Chatterjee 2017), cadmium (Zaborowska et al 2017), copper (Kashulina 2017), mercury , nickel (Plekhanova et al 2017) or trace elements (Hasanuzzaman et al 2017;Saha et al 2017c;Shankar and Shikha 2017).…”
Section: Environmental Pollution and Abiotic Stressmentioning
confidence: 99%